The Role of Family Support in Enhancing Self-Confidence and Business Performance in Women Entrepreneurs - Muh. Arif; Rahmad Solling Hamid (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The performance of businesses owned or operated by women entrepreneurs encompasses the results and accomplishments of these ventures. Evaluating the success and positive impact of women entrepreneurs' managed businesses involves using various metrics and indicators. Factors like self-confidence and family support are potential influencers in shaping women entrepreneurs' business performance. This study explores the interconnection between family support, self-confidence, and business performance among women entrepreneurs. The empirical analysis involved 197 women entrepreneurs surveyed online. After ensuring reliability and validity through tests, the data underwent analysis using partial least squares structural equation modeling. The research findings reveal a significant positive direct impact of family support on self-confidence. Additionally, family support exhibits a notable positive direct influence on business performance. Moreover, self-confidence emerges as a significant positive factor directly affecting business performance.